2022
DOI: 10.3389/fcvm.2022.911649
|View full text |Cite
|
Sign up to set email alerts
|

Whole Exome Sequencing of Patients With Heritable and Idiopathic Pulmonary Arterial Hypertension in Central Taiwan

Abstract: BackgroundGenetic variants could be identified in subjects with idiopathic and heritable pulmonary arterial hypertension (PAH). The 6th World Symposium on Pulmonary Hypertension (WSPH) provided a list of genes with evidence of association with PAH. However, reports using whole exome sequencing (WES) from southeastern Asian PAH cohorts were scarce.MethodsSubjects with idiopathic and heritable PAH (N = 45) from two medical centers in central Taiwan were screened for PAH related gene variants. The genomic DNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…1 To date, no more than 30 cases have been reported at 10 additional variant sites in the AQP1 gene (Figure 2). [4][5][6][7] We recently reported a heterozygous missense variant site c.273C>G (p.Ile91-Met) in a young woman with heritable PAH. 7 Her other two younger siblings also wanted genetic tests, which revealed that they all carried the same variant site of AQP1 c.273C>G. Such test results prompted the middle brother, although initially feeling asymptomatic, to seek medical help and eventually confirmed his diagnosis of PAH.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1 To date, no more than 30 cases have been reported at 10 additional variant sites in the AQP1 gene (Figure 2). [4][5][6][7] We recently reported a heterozygous missense variant site c.273C>G (p.Ile91-Met) in a young woman with heritable PAH. 7 Her other two younger siblings also wanted genetic tests, which revealed that they all carried the same variant site of AQP1 c.273C>G. Such test results prompted the middle brother, although initially feeling asymptomatic, to seek medical help and eventually confirmed his diagnosis of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Location of variants of AQP1 cDNA and related amino acid change detected in subjects with PAH. [4][5][6][7] (b) Representation of the AQP1 protein and the amino acid changes detected in PAH cases. [4][5][6][7] The novel variant (c.273C>G, p.Ile91Met) described in this study was labeled in red font.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations